2021
DOI: 10.3390/ani11051231
|View full text |Cite
|
Sign up to set email alerts
|

The Levels of Mineral Elements and Toxic Metals in the Longissimus lumborum Muscle, Hair and Selected Organs of Red Deer (Cervus elaphus L.) in Poland

Abstract: The aim of the study was to analyse correlations and variability between the levels of mineral elements (Fe, Mn, Zn, Cu, Na, K, Ca and Mg) and toxic metals (Pb and Cd) in the longissimus lumborum muscle, hair and selected organs of red deer (Cervus elaphus L.). The levels of mineral elements were measured using atomic absorption spectroscopy (F-AAS). The levels of Pb and Cd were analysed by means of electrothermal atomic absorption spectroscopy (ET-AAS). Of all analysed microelements, the highest concentration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 31 publications
1
21
0
1
Order By: Relevance
“…In order to investigate the complex relationship between elements, Tables 3 – 5 in the Supplementary information present correlations between selected metals in individual tissues (in the Supplementary Materials ). Similar to this study, negative interactions between Zn and Cu were reported for the hair of red deer by Cygan-Szczegielniak et al ( 2018 ) and by Cygan-Szczegielniak ( 2021 ). A study conducted by Kabata-Pendias and Pendias ( 1999 ) also revealed a metabolically significant antagonism between Zn and Cu, and the competition between these elements for their absorption from the gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In order to investigate the complex relationship between elements, Tables 3 – 5 in the Supplementary information present correlations between selected metals in individual tissues (in the Supplementary Materials ). Similar to this study, negative interactions between Zn and Cu were reported for the hair of red deer by Cygan-Szczegielniak et al ( 2018 ) and by Cygan-Szczegielniak ( 2021 ). A study conducted by Kabata-Pendias and Pendias ( 1999 ) also revealed a metabolically significant antagonism between Zn and Cu, and the competition between these elements for their absorption from the gastrointestinal tract.…”
Section: Discussionsupporting
confidence: 91%
“…In our own research, no clear pattern confirming these relationships was obtained, as was shown in the studies by Garcia et al ( 2011 ). Other research confirmed that hard tissue, including hair, may be an equally good measurement matrix to reflect a degree of heavy metal accumulation (Cygan-Szczegielniak 2021 ; Cygan-Szczegielniak et al 2018 ). Studies conducted by other authors also confirm the use of hard tissue in bioindication techniques.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Heavy metals accumulate in different organs and tissues. They can be detected, for example, in hair, internal organs and muscles [ 2 , 3 ]. Toxic metals such as cadmium or lead pose a serious risk to the proper function of living organisms.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, hair is a more stable analytical matrix, providing a lot of information about a given type of exposure over the years [ 10 , 11 , 12 , 13 , 14 ]. The main advantage of this biological material is its availability, which enables easy, stress-free and non-invasive sampling [ 2 , 3 , 14 , 15 ]. A high concentration of toxic elements in the bodies of livestock may reduce their productivity, performance and metabolism [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%